2017
DOI: 10.1016/j.jmatprotec.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature mechanical properties of electron beam welded zircaloy-4 sheet

Abstract: Resumption of operations at the Transient Reactor Test (TREAT) facility at Idaho National Laboratory was approved in 2014 to meet U.S. Department of Energy Office of Nuclear Energy objectives in transient testing of nuclear fuels. In parallel, the National Nuclear Security Administration, through the Office of Material Management and Minimization, is converting TREAT from its existing highly enriched uranium core to a low-enriched uranium core. This effort entails designing, fabricating, and qualifying a new T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…3 the mechanical properties of EB-welded Zr-4 sheets and observed porosity in the weld joints [19]. Moreover, this porosity formation greatly affects the mechanical and corrosion properties of weld joints.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…3 the mechanical properties of EB-welded Zr-4 sheets and observed porosity in the weld joints [19]. Moreover, this porosity formation greatly affects the mechanical and corrosion properties of weld joints.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…The study by Jha et al [ 18 ] showed that the hardness of Zr-4 alloy electron beam welded joints is higher than that of the BM. The tensile properties of Zr-4 alloy electron beam welded joints are not inferior to those of the parent material [ 19 ], but the presence of pores in the weld may affect the corrosion performance of the joint [ 20 ]. Bandi et al [ 21 ] demonstrated through Raman spectroscopy that the pores in the Zr-4 electron beam welded joint are mainly hydrogen pores.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium (Zr) alloy is widely used in the nuclear and aerospace industries due to its high corrosion resistance, high-temperature stability, excellent mechanical properties, and low thermal neutron absorption cross-section. [1][2][3] In the manufacturing process of these industries, complex structural components often feature overlapping joints composed of multiple layers. Moreover, in critical areas, reinforcing plates are added to ensure manufacturing quality, resulting in a significant number of three-layer or multilayer plate overlap structures.…”
Section: Introductionmentioning
confidence: 99%